VICTIMOLOGY: CONCEPTS AND ITS TYPES - Myhal, Roman Vasylyovych (SUPREMANCE OF LAW, 2018)
This article explores the historical development of the concept of victimology. Victimology is a part of legal science and is considered in the criminological aspect, in criminal law, as well as in general theories.
Keywords: victimology; criminal and criminological victimology